Analisis Penerapan Sistem Bagi Hasil Akad Mudharabah terhadap Pembiayaan pada BSI dan Bank BTPN Syariah - Siska Julian; Nana Diana (Jurnal Ilmiah Wahana Pendidikan, 2023)
Profit sharing is the distribution of the results of operations that have been carried out by the parties to the agreement, namely the customer and the Islamic bank. In this case there are two parties entering into a business agreement, the results of the operations carried out by both parties will be divided according to the portion of each party that has entered into the contract agreement. The purpose of this research is to find out the profit-sharing system for sharia loans in Islamic banking and to find out the benefits of sharia loans. This type of research is a qualitative descriptive research. The data collection techniques used include observation, documentation and interviews. Based on the results of the study, it was concluded that the application of profit sharing for sharia mudharabah contracts by one of the sharia banks, namely Bank BTPN Syariah, uses the profit sharing method because it is more directly used in mudharabah financing. The comparison with other banks is the percentage of profit sharing at the time of entering into a Mudharabah contract agreement. Btpn syariah is a revenue sharing method (revenue sharing) because revenue sharing is considered more beneficial which refers to fatwa no. 15/DSN-MUI/IX/2000. While BSI uses the profit sharing method, both use a financing contract with the mudharabah wal murabahah principle, every month the customer pays installments or installments and the results are shared according to mutually agreed terms.